Minimum Local Anesthetic Dose of Ropivacaine in Cesarean Section for Real-Time Ultrasound-Guided Spinal Anesthesia Using 24-Gauge versus 26-Gauge Needles Based on Fluid Simulation Technology: A Randomized Controlled Trial - Zheng C; Fan H; Ye P; Zhang X; Zheng X; Zheng T (Dove Medical Press, 2024)
Chunying Zheng,1,* Hanliang Fan,1,* Peng Ye,1,* Xing Zhang,1 Xiaochun Zheng,1,2 Ting Zheng1 1Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fujian Provincial Hospital, Fuzhou University Affiliated Provincial Hospital, Fuzhou, People's Republic of China; 2Fujian Provincial Key Laboratory of Emergency Medicine, Fujian Provincial Key Laboratory of Critical Care Medicine, Fujian Provincial Co-Constructed Laboratory of "belt and Road", Fujian Emergency Medical Center, Fuzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaochun Zheng; Ting Zheng, Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, No. 134, Dongjie, 350001, Fuzhou, Fujian, People's Republic of China, Tel +86 8821 7841, Email zhengxiaochun7766@163.com; zhengting1223@163.comPurpose: Previous research has demonstrated that real-time ultrasound-guided (UG) spinal anesthesia requires a higher minimum local anesthetic dose (MLAD) compared to traditional methods. However, the precise MLAD of ropivacaine for UG cesarean sections remains undetermined. In this study, we ascertained the MLAD of ropivacaine for cesarean section. We also investigated the mechanism underlying the diffusion of ropivacaine within the spinal canal using fluid simulation technology.Patients and Methods: We randomly placed 60 healthy parturients undergoing elective cesarean section with real-time UG spinal anesthesia into Groups I (26-gauge spinal needle) and II (24-gauge spinal needle). For the first parturient in both groups, 15 mg of ropivacaine was administered intrathecally. Based on the effective or ineffective response of the previous parturient, the dose for the subsequent parturient was increased or decreased by 1 mg. Spinal anesthesia characteristics and side effects were recorded. A computer-generated spinal canal model was developed. Leveraging fluid dynamics simulation technology, we documented the diffusion of ropivacaine in the spinal canal using 26-and 24-gauge spinal needles.Results: The MLADs in Groups I and II were 12.728 mg (12.339- 13.130 mg) and 9.795 mg (9.491- 10.110 mg), respectively. No significant difference was observed in the onset times and durations of sensory or motor blocks, incidence of complications, or neonatal Apgar scores between both groups. Fluid simulation modeling indicated that the 26-gauge spinal needle achieved a higher distribution level more quickly; however, its peak drug concentration was lower compared to the 24-gauge spinal needle.Conclusion: For cesarean section anesthetization, the required MLAD of ropivacaine when using a real-time UG 26-gauge spinal needle is significantly greater than that with a 24-gauge needle. The spinal needle diameter influences ropivacaine's MLAD by markedly affecting its diffusion rate within the spinal canal.Keywords: anesthetic diffusion, spinal needle diameter, fluid dynamics simulation, cesarean anesthetization